ARSIP PERGURUAN TINGGI SEBAGAI SUMBER KECERDASAN SOSIAL AKADEMIK: INOVASI PENGELOLAAN DI ERA DIGITAL HUMAN-CENTERED - Sanbein, Primus (Khazanah: Jurnal Pengembangan Kearsipan, 2025)
This article aims to formulate a human-centered policy direction for university archival management in response to the challenges and opportunities of digital transformation. Adopting a qualitative-descriptive approach and a review of 38 national and international scholarly articles, this study explores the structural, technological, and philosophical dimensions influencing academic archival governance. The findings reveal that university archives play a strategic role not only as administrative instruments but also as spaces for institutional reflection, social dialogue, and the cultivation of collective intelligence within academic communities. Concepts such as collective intelligence, semantic systems, and participatory curation provide the foundation for inclusive and sustainable policy alternatives. This paper proposes five strategic directions: digital curation training, implementation of AI-based metadata systems, adoption of open interoperability models, institutionalization of campus-based digital curation units, and development of ethical guidelines grounded in inclusion and the right to memory. Through this approach, university digital archives can evolve into adaptive, reflective, and humanistic epistemic infrastructures that strengthen institutional memory resilience in the Society 5.0 era.